Teaching History Through Theater: The Effects of Arts Integration on Students' Knowledge and Attitudes - Brian Kisida; Laura Goodwin; Daniel H. Bowen (SAGE Publishing, 2020)
Faced with accountability pressures and limited resources, education policymakers make difficult choices regarding school curricula. In recent years, studies have documented a decreased emphasis in arts and humanities instruction. One potential way for schools to fill this gap includes partnering with arts and cultural organizations to provide arts learning opportunities through arts integration, yet there is limited evidence on the effectiveness of such programs. We examine one such partnership by evaluating the efficacy of a program that infuses history content with theater. By randomly assigning school groups to participate in this program, we are able to draw causal conclusions about its effects. We find that students demonstrate increases in historical content knowledge, enthusiasm for learning about history, historical empathy, and interest in the performing arts as a result of this program. These findings suggest that there are valuable educational benefits from arts-integrated learning opportunities provided through school partnerships with arts organizations.